CSF AD‐like profile in SCD, pre‐MCI and MCI subjects: Application of the A/T/N classification model in a retrospective cohort from a memory clinic: Neuropsychology/Neuropsychological correlates of physiologic markers of cognitive decline/Dementia. (7th December 2020) - Chipi, Elena; Salvadori, Nicola; Bellomo, Giovanni; Biscetti, Leonardo; Farotti, Lucia; Lisetti, Viviana; Montanucci, Chiara; Cataldi, Samuela; Parnetti, Lucilla
Abstract: Background: Subtle deficits not fulfilling Mild Cognitive Impairment (MCI) can be associated with pathophysiological AD biomarkers positivity and higher risk of clinical progression (Parnetti et al., 2019). Several attempts have been carried out in order to characterize neuropsychological features and Alzheimer's disease (AD) biomarkers in pre‐MCI populations (Chipi et al., 2019). We aimed to explore, by applying the A/T/(N) classification scheme (Jack et al., 2018), the prevalence of cerebrospinal fluid (CSF) AD‐like profile (A+/T+) in a cohort of subjective cognitive decline (SCD), pre‐MCI and MCI subjects. Method: Seventy‐six consecutive patients (34 M; 42F; mean age: 68.7 years; mean education: 10.7 years), referred to our Memory Clinic from 2016 to 2019, were defined as SCD (n.11) (Jessen et al., 2014), pre‐MCI (n. 28) (Duara et al., 2011) and MCI (n.37) (Albert et al., 2011) by means of an advance neuropsychological battery and underwent lumbar puncture for the analysis of CSF core AD biomarkers (Aβ42/Aβ40 ratio, total tau, phospho‐tau). According to the cut‐off used in our lab, we considered Aβ42/40 ratio <0.069 as A+, phospho‐tau >70 pg/mL as T+, total tau > 400 pg/mL as N+. Result: No differences were found in age, gender and education among groups. AD‐like CSF profile (A+T+) was found in 10.7% of pre‐MCI and in 54.1% of MCI (p<0.001). None of SCD subjects showed AD‐like profile. Prevalence of A+ was found in 9.1% of SCD and 35.7% of pre‐MCI, compared to 73% of MCI (SCD vs MCI: p<0.001; pre‐MCI vs MCI: p=0.0049). Conclusion: Consistent proportion (10.7%) of subjects with subtle cognitive deficits not fulfilling MCI (pre‐MCI) in our cohort showed evidence of AD‐like profile, while none of SCD resulted A+/T+. Amyloidosis was detectable in both SCD and pre‐MCI subjects. Accordingly, pre‐MCI with evidence of AD‐like biomarkers may be considered as the earliest clinical manifestation of AD, and may represent an important target for treatment with disease‐modifying drugs.